2017
DOI: 10.1007/s00394-017-1387-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorella vulgaris on tumor growth in mammary tumor-bearing Balb/c mice: discussing association of an immune-suppressed protumor microenvironment with serum IFNγ and IgG decrease and spleen IgG potentiation

Abstract: Our data provided evidence that C. vulgaris at a specific dose (200 mg/kg) promoted tumor growth in a mammary tumor model. This consequence might reflect an immune derangement in favor of developing a protumor microenvironment. However, this hypothesis needs to be further investigated in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The mRNA copy numbers of seven genes within tumor tissues were measured by real‐time PCR using specific pairs of primers, the oligonucleotide sequences of which are as follows (Khalilnezhad et al, ): GAPDH forward 5′‐AACGACCCCTTCATTGAC‐3′ and GAPDH reverse 5′‐TCCACGACATACTCAGCAC‐3′; heme oxygenase‐1 (HO‐1) forward 5′‐CAGAAGAGGCTAAGACCGCCTT‐3′ and HO‐1 reverse 5′‐TCTGGTCTTTGTGTTCCTCTGTCA‐3′; IFN‐γ forward 5′‐GCTTTAACAGCAGGCCAGAC‐3′ and IFN‐γ reverse 5′‐GGAAGCACCAGGTGTCAAGT‐3′; fibroblast growth factor 2 (FGF2) forward 5′‐CCGGTCACGGAAATACTCCA‐3′ and FGF2 reverse 5′‐CCTTCTGTCCAGGTCCCGTT‐3′; VEGFa forward 5′‐TCGCTCCTCCACTTCTGAGG‐3′ and VEGFa reverse 5′‐GGCCATTACCAGGCCTCTTC‐3′; VEGFR2 forward 5′‐AGATGCATTGTGCTGGCTCT‐3′ and VEGFR2 reverse 5′‐AACTCGCCTGTAACCCGACT‐3′; and Cyclooxygenase‐2 (COX2) forward 5′‐TTGGAGCACCATTCTCCTTG‐3′ and COX2 reverse 5′‐AGGTGCTCGGCTTCCAGTAT‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…The mRNA copy numbers of seven genes within tumor tissues were measured by real‐time PCR using specific pairs of primers, the oligonucleotide sequences of which are as follows (Khalilnezhad et al, ): GAPDH forward 5′‐AACGACCCCTTCATTGAC‐3′ and GAPDH reverse 5′‐TCCACGACATACTCAGCAC‐3′; heme oxygenase‐1 (HO‐1) forward 5′‐CAGAAGAGGCTAAGACCGCCTT‐3′ and HO‐1 reverse 5′‐TCTGGTCTTTGTGTTCCTCTGTCA‐3′; IFN‐γ forward 5′‐GCTTTAACAGCAGGCCAGAC‐3′ and IFN‐γ reverse 5′‐GGAAGCACCAGGTGTCAAGT‐3′; fibroblast growth factor 2 (FGF2) forward 5′‐CCGGTCACGGAAATACTCCA‐3′ and FGF2 reverse 5′‐CCTTCTGTCCAGGTCCCGTT‐3′; VEGFa forward 5′‐TCGCTCCTCCACTTCTGAGG‐3′ and VEGFa reverse 5′‐GGCCATTACCAGGCCTCTTC‐3′; VEGFR2 forward 5′‐AGATGCATTGTGCTGGCTCT‐3′ and VEGFR2 reverse 5′‐AACTCGCCTGTAACCCGACT‐3′; and Cyclooxygenase‐2 (COX2) forward 5′‐TTGGAGCACCATTCTCCTTG‐3′ and COX2 reverse 5′‐AGGTGCTCGGCTTCCAGTAT‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…1B). The spleen, which is the largest peripheral lymphoid organ and contains numerous immunologically active cells and immune factors, may explain differences in these data [ [34] , [35] , [36] ]. Sepsis occurred rapidly in splenectomized mice, and they had reduced pneumococcal clearance [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of dried Chlorella pyrenoidosa powder on the development of diethylnitrosamine-induced hepatocarcinogenesis in rats was reported by Takekoshi et al [19]. On the contrary, research conducted on mammary tumour-bearing mice strain Balb/c by Khalilnezhad et al revealed that powder of Chlorella vulgaris administered to mice for 42 days at a dose of 200 mg/kg promoted tumour growth, while other investigated concentration (300 mg/kg) did not affect the analyzed process [20].…”
Section: Introductionmentioning
confidence: 92%